Volume 3: 17th International Conference on Advanced Vehicle Technologies; 12th International Conference on Design Education; 8t 2015
DOI: 10.1115/detc2015-47650
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional and Longitudinal Examination of the Development of Innovation Capability in Undergraduate Engineering Students

Abstract: Multiple research studies have examined the role of the undergraduate engineering curriculum on students’ innovation capabilities. The majority of these studies have used cross-sectional samples to compare students at the beginning and end of their college careers, and most results have shown that seniors outperform freshmen. In the following paper, we use a combination of cross-sectional and longitudinal comparisons to uncover when innovation capabilities grow. Over a two-year period, undergraduate engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…This was found to be true for design tasks that were subjectively intended to be ‗equivalent'. Interestingly, Kershaw, et al (2015) also found that the semester in which an engineering student is given a particular design problem can affect the creativity of the generated ideas. While these studies illustrate that the type, and timing, of a design problem in engineering education may impact student creativity training (see discussion in (Kremer, et al, 2011)), few studies have explored the impact of the design task being explored in the phases following idea generation.…”
Section: The Impact Of the Design Task In Engineering Educationmentioning
confidence: 99%
“…This was found to be true for design tasks that were subjectively intended to be ‗equivalent'. Interestingly, Kershaw, et al (2015) also found that the semester in which an engineering student is given a particular design problem can affect the creativity of the generated ideas. While these studies illustrate that the type, and timing, of a design problem in engineering education may impact student creativity training (see discussion in (Kremer, et al, 2011)), few studies have explored the impact of the design task being explored in the phases following idea generation.…”
Section: The Impact Of the Design Task In Engineering Educationmentioning
confidence: 99%
“…This result could, but does not necessarily, indicate a more comprehensive understanding of innovation among the less experienced first-year students. In a follow-up study, however, Kershaw and colleagues 19 found no significant group differences between first-year and senior students. In longitudinally comparing students on the same task during their junior and senior year, Kershaw and colleagues also found that students uniformly outperformed their junior scores as seniors.…”
Section: Research On How Students View Approach and Output Innovatimentioning
confidence: 87%
“…Novelty: We assessed novelty by using a decision tree. The approach we used to calculate this method is closely modeled after the decision trees used by Kershaw et al [62], which is adapted from the creative engineering design assessment (CEDA) approach [63]. We favored this approach over feature-level measures of novelty because many concepts simply did not give enough information to be broken down into features.…”
Section: 3mentioning
confidence: 99%
“…Quality: Shah argues that any method can be used [11] to measure quality, but recommends a weighted decision matrix. Because many concepts could not be broken down into features, we again measured quality at the concept-level by adapting the decision trees used by Kershaw et al [62]. The decision tree we used is shown in Fig.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation